Elementary School Children’s IQ Levels Due to the Prevalence of Stunting - Welis, Wilda; Khairuddin; Darni (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to analyze the IQ levels due to the prevalence of stunting in primary school students. It is a cross-sectional research approach covering 50 elementary school students chosen by a purposive sampling technique. The data were collected by measuring students’ height and applying the Wechsler Intelligence Scale for Children (WISC) method. The independent samples t-test was used to analyze the data. The results of this research showed that the mean of students’ age was 7.81 + 0.9 years old, the mean of students’ weight was 19.81 + 4.3 kg, and the mean of students’ height was 116.71 + 7.1 cm. Besides, 24 students suffered from stunting, and the other 26 students were typical. For students with stunting, the mean of students’ IQ level was 79.31+14.7. For typical students, the mean of students’ IQ was 81.41+12.5. Therefore, it can be concluded that stunting students and non-stunting students do not differ in terms of IQ levels.